Pengaruh model pembelajaran, gaya kognitif dan kemampuan awal terhadap hasil belajar matematika Siswa SMPN 1 Rantepao - Duma, Sonny Yalti (Universitas Negeri Makassar, 2017)
This research is experimental research that aims to determine whether the model of learning, cognitive style and ability to influence the outcome of learning early math class VIII SMP Negeri 1 Rantepao. Population in this research is class VIII SMP Negeri 1Rantepao. The instrument used in this study was the observation sheets, questionnaires, mathematics achievement test that includes pre-test and post-test, test early and test the ability of cognitive style (Test GEFT). The data obtained were analyzed using descriptive statistics and inferential statistical analysis using linear regression with interaction factors. The results showed that students' mathematics learning outcomes are influenced by a model of learning, cognitive styles and abilities early.